UJI ORGANOLEPTIK KESEGARAN IKAN LAYANG (Decapterus, sp) SELAMA PENANGANAN SUHU DINGIN - Ainul Mardiah; Indira Karina; Eddwina Aidila Fitria (SEMAH Jurnal Pengelolaan Sumberdaya Perairan, 2022)
Handling the layang fish (Decapterus sp) cold chain is an effort to maintain the freshness of fish until it reaches consumers in a fresh condition. Added ice flakes are the method for applying low temperatures in storage so that fish are durable and long-lasting. The purpose of this study was to analyze the freshness level of layang fish after being stored for 0, 2, 4, and 6 hours. The study used an experimental method with four treatments and three replications. Fish samples were taken directly from Tempat Pelelangan Ikan (TPI) Bungus, Padang, and transported to the laboratory using a cold box. On arrival at the laboratory, the fish samples were separated into several cold boxes which had been given ice flakes with the ratio of fish to ice 1:1. Then, the organoleptic test was carried out using 25 semi-trained panelists. The organoleptic parameters were eyes, gills, mucus, fish cutlet, odor, and texture of layang fish. The results showed that chilled storage for 2-4 hours found that layang fish was still categorized as fresh and received a score of 6.00 – 7.48 from the panelists, meaning that fish was highly favored by consumers. After 6 hours of chilled storage, the quality of fish began to decline with an average score ranging from 4.72-5.20 with the characteristics of fish eyes turning red and the fish flesh becoming mushy. Handling chilled temperatures is necessary to maintain the quality and freshness of layang fish. The best-chilled storage temperature was about 2-4 hours.